Comparison of 3 Port vs 4 Port Laparoscopic Cholecystectomy for Gallstone Disease - Shafiq, Mahrukh; Kumar, Rohit; Ali, Aun; Zia, Muhammad Khurram; Iqbal, Mansoor; Lakdawala, Yousuf (Biological and Clinical Sciences Research Journal, 2025)
Laparoscopic cholecystectomy (LC) is the gold standard for treating symptomatic gallstones. Conventionally performed with four ports, the three-port modification has been proposed to reduce surgical trauma, postoperative pain, and recovery time. However, evidence comparing the safety and outcomes of three-port versus four-port LC in the Pakistani population remains limited. Objective: To evaluate and compare the clinical outcomes and perioperative risks of three-port LC with four-port LC. Methods: This randomised comparative study was conducted at F.R.P.M.C. PAF Hospital, Karachi, from 1 August 2023 to 1 July 2024, following ethical approval. A total of 60 patients aged 18–60 years of both genders, classified as ASA I or II, and scheduled for elective LC were recruited through non-probability consecutive sampling. Patients were randomised into two groups: three-port LC and four-port LC. Intraoperative complications, conversion to open surgery, length of hospital stay, postoperative pain (assessed by a standardised pain score), and recovery time were compared. Statistical analysis was performed using appropriate parametric and non-parametric tests, with p<0.05 considered significant. Results: Intraoperative complications were lower in the three-port group compared with the four-port group (17% vs. 40%, p=0.09). Conversion to open surgery occurred in 27% of three-port and 40% of four-port cases (p=0.255). The mean hospital stay was significantly shorter in the three-port group (2.8±0.6 days) than in the four-port group (3.5±0.7 days) (p<0.0001). Postoperative pain scores were also significantly lower in the three-port group (5.7±0.9) compared to the four-port group (6.5±0.9) (p=0.001). Furthermore, recovery time was faster in the three-port group (14.9±1.4 days) compared with the four-port group (17.2±1.5 days) (p<0.0001). Conclusion: Three-port LC is a safe and effective alternative to conventional four-port LC, offering shorter hospitalisation, reduced postoperative pain, faster recovery, and enhanced patient satisfaction, without increasing intraoperative risks.